PHACTR1, a coronary artery disease risk gene, mediates endothelial dysfunction - Ma, Xiaoxuan; Su, Meiming; He, Qingze; Zhang, Zhidan; Zhang, Fanshun; Liu, Zhenghong; Sun, Lu; Weng, Jianping; Xu, Suowen (Frontiers in Immunology, 2022)
Genome-wide association studies (GWAS) have recently identified phosphatase and actin regulator-1 (PHACTR1) as a critical risk gene associated with polyvascular diseases. However, it remains largely unclear how PHACTR1 is involved in endothelial dysfunction. Here, by mining published datasets of human stable and vulnerable/ruptured plaque tissues, we observed upregulated expression of PHACTR1 in vulnerable/ruptured plaques. Congruent with these data, we demonstrated increased Phactr1 gene expression in aortic endothelium from ApoE-/- mice fed a western type diet compared with that in normal C57BL/6J mice. Relevantly, PHACTR1 gene expression was upregulated by pro-inflammatory and pro-atherogenic stimuli, including TNF-α, IL-1β and oxidized LDL (oxLDL). By employing next-generation RNA sequencing, we demonstrate that PHACTR1 overexpression disrupts pathways associated with endothelial homeostasis. Cell biological studies unravel that PHACTR1 mediates endothelial inflammation and monocyte adhesion by activating NF-κB dependent intercellular adhesion molecule 1 (ICAM1) and vascular cell adhesion molecule 1 (VCAM1) expression. In addition, overexpression of PHACTR1 also reduces the generation of nitric oxide (NO) by inhibiting Akt/eNOS activation. In-house compound screening of vasoprotective drugs identifies several drugs, including lipid-lowering statins, decreases PHACTR1 gene expression. However, PHACTR1 gene expression was not affected by another lipid-lowering drug-fenofibrate. We also performed a proteomic study to reveal PHACTR1 interacting proteins and validated that PHACTR1 can interact with heat shock protein A8 (HSPA8) which was reported to be associated with coronary artery disease and eNOS degradation. Further studies are warranted to confirm the precise mechanism of PHACTR1 in driving endothelial dysfunction. In conclusion, by using systems biology approach and molecular validation, we disclose the deleterious effects of PHACTR1 on endothelial function by inducing endothelial inflammation and reducing NO production, highlighting the potential to prevent endothelial dysfunction and atherosclerosis by targeting PHACTR1 expression. The precise role of endothelial cell PHACTR1 in polyvascular diseases remains to be validated in diseased conditions.